2010
DOI: 10.1128/jcm.02301-09
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes Associated with Acquisition of Colistin-Resistant KPC-Producing Klebsiella pneumoniae : a Matched Case-Control Study

Abstract: A matched 1:3 case-control study investigated factors predicting colistin-resistant versus colistin-susceptible KPC-producing Klebsiella pneumoniae acquisition and its impact on patient outcomes. Case patients were more often admitted from other institutions (P ‫؍‬ 0.019) and had longer therapy with ␤-lactam/␤-lactamase inhibitors (P ‫؍‬ 0.002) and higher overall mortality (P ‫؍‬ 0.05). All 52 study isolates were clonally related, suggesting horizontal dissemination. None of these parameters independently pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 15 publications
3
72
3
3
Order By: Relevance
“…These data revealed that in most cases (35 of 38; 92%), the patient had not received colistin prior to isolation of COL r CRKP (since admission or, in case of prolonged or repeated admissions, for a period of up to 3 months), while in only 3 cases had the patient received colistin (range, 5 to 32 days). These findings are in agreement with previous observations from smaller outbreaks (21,22).…”
supporting
confidence: 83%
“…These data revealed that in most cases (35 of 38; 92%), the patient had not received colistin prior to isolation of COL r CRKP (since admission or, in case of prolonged or repeated admissions, for a period of up to 3 months), while in only 3 cases had the patient received colistin (range, 5 to 32 days). These findings are in agreement with previous observations from smaller outbreaks (21,22).…”
supporting
confidence: 83%
“…Infections caused by KPC-or MBL-producing K. pneumoniae have been associated with severity of underlying disease, age, diabetes mellitus, ICU admission, mechanical ventilation, and exposure to cephalosporins, carbapenems, and fluoroquinolones [Gasink et al 2009;Hussein et al 2009;Moloudi et al 2010;Zarkotou et al 2010;Chitnis et al 2012;Tuon et al 2012].…”
Section: Individual Risk Factorsmentioning
confidence: 99%
“…However, in the past few years resistance to these compounds has begun to emerge: cases of KPC colistin-resistant have been reported from various parts of the world, e.g. Greece (12,13), Israel (14), South Korea (15), United States (16) and recently also in Italy (17). The multiresistent K. pneumoniae strains have been generally attributed to the international epidemic clone ST258 (18,19).…”
mentioning
confidence: 99%